Analysis Of The Influence Of Fake Discount Price Labels For A Product In The Marketplace On The Concept Of Business Competition And Responsibility - Erwina, Liza; Nurmalawaty, Nurmalawaty; Hasibuan, Syafruddin sulung (PT. Anagata Sembagi Education, 2024)
: This study examines the fulfillment of the defendant's human rights during the judicial process in a premeditated murder case, based on Decision No. 319/Pid.B/2023/PN Smr. The case revolves around the defendant, who was accused and found guilty of premeditated murder. The study delves into various aspects of the judicial process, including the arrest, detention, trial proceedings, and the final verdict. It evaluates whether the defendant's rights were upheld in accordance with national and international human rights standards. Key findings highlight areas of compliance and potential violations, providing insights into the judicial system's handling of serious criminal cases. The research aims to contribute to the ongoing discourse on human rights within the Indonesian judicial framework, emphasizing the importance of safeguarding the rights of all individuals involved in criminal proceedings. This comprehensive analysis seeks to shed light on the effectiveness of existing legal protections for defendants, drawing attention to both strengths and weaknesses in the current system. Ultimately, the study underscores the necessity of continuous improvement in ensuring justice and human rights for all parties in criminal cases.